Biochemical markers of bone turnover in tibia fracture patients randomly assigned to growth hormone (GH) or placebo injections - Krusenstjerna-Hafstrøm, Thomas; Rasmussen, Michael Højby; Raschke, Michael; Govender, Shunmugam; Madsen, Jesper; Christiansen, Jens Sandahl (Growth hormone & IGF research, 2011)
It has been argued that increased levels of bone remodelling markers are not suitable indicators of GH abuse, as bone injuries per se increase the expression levels of these markers. To investigate the impact of a recovering tibia fracture on circulating bone markers in subjects receiving placebo or GH treatment. A randomised, double-blind, placebo-controlled trial of up to 16 weeks GH treatment, followed by a 16-week washout. Subjects (406 adult males and females) with a tibia fracture were randomly allocated within three days after surgery, to either placebo or GH treatment (15, 30 or 60 μg/kg daily) until fracture healing or 16 weeks after treatment initiation. IGF-I, serum C-terminal telopeptide of type I collagen (CTX), osteocalcin (OST) and bone-specific alkaline phosphatase (BAP) were measured during and after treatment. Dose-dependent increases were observed in groups receiving GH, and mean levels in the highest GH dose group peaked at eight (IGF-I, CTX) or 12 weeks (OST) after treatment initiation. Statistically significant differences between GH treatment and placebo were seen for IGF-I, CTX and OST in all GH dose groups throughout the treatment period, and persisted until eight (CTX) or 12 (OST) weeks after cessation of treatment. IGF-I, CTX and OST are suitable candidate markers of prolonged, illicit administration of GH. Furthermore, CTX and OST have potentials to serve as markers also after cessation of GH administration.